CASE REPORT: MUCOLIPIDOSIS BONE DISEASE RESEMBLING NEONATAL RICKETS - Boo, Jian Ann; Teoh, Sze Teik; Ang, Eric Boon Kuang (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION/BACKGROUND Mucolipidosis II (I-cell disease) is a rare genetic metabolic disorder of lysosomal metabolism with a combined frequency of 1:422,000, that is characterized by coarse facial features, disproportionate short stature, hyperplastic gums, organomegaly, and retarded psychomotor development. These physical changes however require time to develop and are not apparent at birth. Opportunistically, neonates with I-cell disease are diagnosed after revealing typical spine changes in skeletal survey. Unlike nutritional rickets, their underlying cause and course of the bone disease are different. CASE We report a premature 34-week-old male with a birth weight of 1.6 kg. He was born in an ambulance while his mother was being transferred from a district hospital. He required cardiopulmonary resuscitation at birth and was admitted to the neonatal intensive care unit where he stayed for another 6 months due to respiratory reason. During his 1st to 4th months of life, he had markedly raised ALP level (>1000 IU/L), together with severe hyperparathyroidism that gradually resolved with time. He had radiographic changes resembling rickets which persisted and progressed to “chronic osteitis fibrosa cystica”. His serum calcium, phosphate, and 25(OH)D3 levels had always been normal. He never had a fracture. His diagnosis was later confirmed by marked elevation of plasma b-hexosaminidase, b-mannosidase and a-mannosidase. He was discharged home with tracheostomy and CPAP. He continues to survive at 11 months old by the time of this report. CONCLUSION Mucolipidosis osteodystrophy could resemble nutritional rickets during the neonatal period but it is not related to either deficient vitamin D or minerals. Failure to respond to conventional treatment (vitamin D and calcium or phosphate), should prompt for a search for other causes of increased bone turnover. In I-cell disease, hyperparathyroidism often remits but bone disease progresses. Bisphosphonate therapy such as pamidronic acid has been described in those with recurrent fractures in later life.